EFL STUDENT’S POLITENESS STRATEGIES IN THE ANALYSIS DISCOURSE CLASSROOM (Universitas Negeri Semarang, 2022)
This study aimed to explore pragmatic politeness by Brown and Levinson which was practiced by two English department students in the 6th semester in teacher college on the process presentation of discourse analysis classroom. Politeness is one of the most researched areas in contemporary pragmatics. Politeness studies which identify deeply about English students’ strategies are still limited and therefore, need to be explored further. The data collection was compiled by observation and Data recording and the data analysis technic used data collection, data reduction, data display, and conclusion. In the opening activity, the findings showed that 2 presenters used positive politeness strategies in the form of greeting and thanking expressions. Bald on-record in the form of task-oriented, request, and alerting. The analysis showed that positive politeness strategies have the highest frequencies. Then, followed by bald on-record strategies in number 2, Negative politeness and off-record strategies did not use.